Exploring the Phytochemical Potential of Erythrina Species: A Review on Extraction Methods and Bioactive Properties - Muhammad, N.; Abu Bakar, F.I.; Abu Bakar, M.F.; Sabran, S.F.; Pa’ee, F.; Talip, B.H.A.; Zamri, A.Z.M.; Rahim, N.F.A.; Karim, R.A.; Zainol, N.Z.N.; Razak, A.H.A.; Ahmad, R. (Asian Journal of Chemistry, 2025)
Erythrina species, are well-known for their abundance of medicinal properties such as antioxidant, anti-inflammatory, antibacterial and anticancer due to their bioactive compounds. This article aims to provide a brief review on the impact of different extraction methods, from traditional techniques (e.g. Soxhlet extraction; maceration), to newer and more eco-friendly approaches (e.g. ultrasound-assisted extraction (UAE); microwave-assisted extraction (MAE)) on the bioactivities. A review was done using databases such as PubMed, Scopus, Web of Science and Google Scholar, searching for terms like Erythrina genus, extraction method, extraction conditions, phytochemicals and bioactivities. As a result, 5 different extraction methods were found to be the most frequently used for extraction of Erythrina species, which are Soxhlet extraction, maceration, decoction, UAE and MAE. It was also showed that UAE and MAE are the most ideal extraction techniques as it improved extraction efficiency, preserve bioactive compounds and increased bioactivity retention. Hence, this mini-review is a discussion on the influence of extraction condition such as extraction temperature and extraction time that may affect the bioactivity of Erythrina species from the previous studies.